2022
DOI: 10.30822/arteks.v7i1.1457
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of meaning in mosque architecture: A case study of old and modern mosques in West Java Indonesia

Abstract: Humans are homo religiosus with a natural desire that there is an absolute power beyond reasoning which makes them "existent". This is observed from their religious behaviors as well as the continuous increase in their spirituality. Humans have a basic need to worship according to their religious orders and the construction of mosques is considered the fulfillment of the main needs of Muslims to conduct their prayers. The diversity of mosque forms in West Java showed that there is a mutually influencing relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The design of this mosque attempted to break free from tradition and reinterpret the essence of architectural locality. It emphasized simplicity, and functionality, minimized ornamentation, showcased the honesty of materials (Dewiyanti & Budi, 2015), and explored aspects of function and meaning based on modern ideologies and spirits (Astrina & Indrarani, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of this mosque attempted to break free from tradition and reinterpret the essence of architectural locality. It emphasized simplicity, and functionality, minimized ornamentation, showcased the honesty of materials (Dewiyanti & Budi, 2015), and explored aspects of function and meaning based on modern ideologies and spirits (Astrina & Indrarani, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Dewiyanti & Budi (2015) explain in more detail in the table: (Table 2) The Salman Mosque emerged as a generator of modernism in several aspects: it was the first mosque that differed from its predecessors, its structural design employed computer technology, and the opinions of the mosque's architect, Achmad Noe'man, indicated that modern architecture represented Islam moving towards modernization (Dewiyanti & Budi, 2016). However, the expected influence of modernization envisioned by the architect (Achmad Noe'man) did not significantly impact mosque architecture in Indonesia, partly due to the limited scope (in terms of function, form, and meaning) of the principles applied (Astrina & Indrarani, 2022). According to Asy Syahid (2018), the significant aspect of mosque modernization is the focus on its interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…There is a wave or hanging bee carving at the stairs. The curving symbolizes hope and persistence in struggling, and the curve line symbolizes the human life journey that is always in the fate circle [14]. There are also ornaments on the wall of Rumah Lontiok namely the Gondo Ari carving.…”
Section: Water Reservoirmentioning
confidence: 99%
“…Several studies related to mosque architecture in the world, predominantly focusing on cosmological, cultural, and ideological meanings that influence the interpretation of mosques, have been carried out by researchers [5] [6]. One study related to mosque architecture in West Java stated that mosque architecture was influenced by the wishes of pious worshipers and the personal desires of the architecture [7]. Although the architecture of the Kajoran mosque is relatively close to the kingdom's territory, in detail, the architecture and the surrounding life have differences.…”
Section: Introductionmentioning
confidence: 99%